Comparison of Ultrasonography and Intravenous Urography in the Screening and Diagnosis of Hematuria Causes - Rajaie Esfahani, Mohammad; Momeni, Ali (Urology Journal, 2009)
Introduction: Our aim was to compare transabdominal ultrasonography (US) and intravenous urography (IVU) in the evaluation of patients with hematuria. Materials and Methods: Two hundred patients with hematuria were assessed by US and IVU, and if needed, by cystoscopy, ureteroscopy, and CT scan, to determine the definite cause of hematuria. The results of US and IVU were compared according to the definite diagnoses. Results: Of 97 patients with microscopic hematuria, 44 (45%) had a documented cause for hematuria, and of 103 patients with gross hematuria, 76 (74%) had a definite disorder (P < .001). Urinary calculi were found in 105 patients, 93 (88.5%) and 73 (69.5%) of which were detected by US and IVU, respectively (P < .001). There were 3 and 6 cases of kidney and bladder neoplasms, respectively, all of which were revealed by US, but only 2 renal tumors were detectable on IVU. Ultrasonography had a higher sensitivity than IVU for diagnoses of kidney calculi, lower ureteral calculi, and urologic neoplasms (95.3% versus 65.1% for kidney calculi, P = .039; 89.7% versus 69.2% for lower ureteral calculi, P < .001; and 100% versus 22.3% for urologic neoplasms, P < .001), but in calculi of the middle and upper ureter and of the whole ureter, there were no differences between US and IVU.Â Conclusion: Our results are in favor of using US in the initial evaluation of hematuria. However, we must choose our diagnostic tool according to the patientâ€™s condition and suspected disorders causing hematuria.